Parameters identification of photovoltaic modules for estimating the power generated under non-standard conditions. (2nd October 2017) - Aristizábal, Andrés Julián; Páez, Carlos Arturo; Chica, Alonso de Jesús
Abstract: The initial context of this work is to evaluate the power production of solar panels under different conditions of solar radiation and temperature in order to have simulation tools to analyze the performance of photovoltaic systems. This work describes a mathematical procedure developed for estimating the power delivered by building integrated photovoltaic (BIPV) systems operating under non-standard conditions of irradiance and temperature. The model was implemented using the Matlab software, and it uses the electrical circuit equivalent of a solar cell of a single diode, which allows obtaining the curves I–V, P–V of a photovoltaic module for different levels of solar radiation and temperature. The results are compared with the data reported by the manufacturer, by calculating the percentages of relative error at the point of maximum power. It is also possible to calculate the characteristics of electrical power to the full BIPV system under standard conditions of 1000 W/m 2 and 25 °C.